RESHAPING THE WTO DISPUTE SETTLEMENT SYSTEM: CHALLENGES AND OPPORTUNITIES FOR DEVELOPING COUNTRIES IN THE DOHA ROUND NEGOTIATIONS - Kazzi, Habib (European Scientific Journal, ESJ, 2015)
The reform of the WTO Dispute Settlement System is an integral part of the Doha Development Agenda launched at the WTO’s Fourth Ministerial Conference in 2001.While the World Trade Organization is marking its 20th anniversary, the modernization process tends to reinforce the WTO legitimacy and to bring developing countries into the world economy in a fairer and more efficient way. On January 30th, 2015, the Special Session of the Dispute Settlement Body, chaired by H.E. Ronald S. Soto, issued its latest report providing a state-of-play of the negotiations in this area. In light of the above, this paper brings to light both developing country interests in the current talks and the remaining challenges for their better integration into the Dispute Settlement System.